Controls on sublithospheric small-scale convection on Curie depths - Likerman, Jeremias; Zlotnik, Sergio; Chun Feng, Li
As the ocean lithosphere cools and thickens, its bottom layer goes unstable leading to sub-lithospheric small-scale convection (SSC). Since SSC was originally proposed, there have been considerable efforts regarding the understanding of the physics that rules the thermal instabilities of the SSC (e.g. Dumoulin et al, 1999; Solomatov and Moresi, 2000). Over the last several years, it is understood that the interaction between the plate movement and the SSC tends to form longitudinal (LRs or also called ?Richter rolls?) and transverse rolls (TRs), of which the axis is parallel and perpendicular to the plate motion, respectively. The geometry of these rolls have been been recently inferred by Li et al (2013) using Curie depths from the North Atlantic as proxies for plates temperatures. They showed that Curie depths have a large oscillating and heterogeneous patterns that could be related to SSC. In the North Atlantic transverse rolls seem predominant. In this work we analyze, by means of 3D dynamical numerical simulations, the influence of SSC on the Curie depths patterns observed in the North Atlantic and Pacific plates. We investigate the behaviour of the Curie isotherms trying to determine if SSC is able to reproduce the observed data, and the influence of several poorly constrained rheological parameters.Our numerical simulations show that: a) using realistic laboratory-constrained rheologies and temperature it is possible to modify temperatures as low as those at Curie depths; b) transverse rolls are generated as well as longitudinal rolls on those isotherms; c) the spreading rate is a first order control on the developing of transverse rolls. Fil: Likerman, Jeremias. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Estudios Andinos "Don Pablo Groeber". Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Estudios Andinos "Don Pablo Groeber"; Argentina Fil: Zlotnik, Sergio. Universidad ...